Insecurity Territorialities and Biopolitical Strategies of the Guarani and Kaiowá Indigenous Folk on Brazil’s Borderland Strip with Paraguay - Marcos Mondardo (L'Espace Politique)
This paper discusses the matter about the insecurity territorialities of the Guarani and Kaiowá indigenous folk on the context of indigenous territories demarcation in the state of Mato Grosso do Sul, on the Brazilian borderland strip with Paraguay. It is discussed about the biopolitical strategies of alternative territorializing on camps and the territorial arrangements of struggle for land and human rights, especially the temporary closure of roads and the multi/transterritorial transit across the border.